Managing the Flood Waves from Hemrin Dam - Hajir Majid Ghali; Riyadh Z. Azzubaidi (Journal of Engineering, 2021)
Diyala Governorate was exposed recently to high flood waves discharged from Hemrin Dam to Diyala River when the dam reached its full capacity. The recently recorded discharge capacity of Diyala River was reduced to just 750m3/s. This exposes cities and villages along the Diyala River to flood risk when discharging the flood waves, which may reach 3000 m3/s. It is important to manage, suggest, and design flood escapes to discharge the flood waves from Hemrin Dam away from Diyala River. This escape branches from Hemrin Lake towards Ashweicha Marsh. One dimensional hydraulic model was developed to simulate the flow within the escape by using HEC-RAS software. Eighty-two cross-sections were extracted from the digital elevation model for the escape and used as geometric data. Moreover, thirty cross-sections for the Diyala River were utilized from the Strategic Study for Water and Land Resources in Iraq. Since the escape passes through two regions of different geological formations, two roughness coefficients of 0.035and0.028were used. Two discharge cases were applied3000m3/s, which is the 500 years return period extreme hydrograph of Hemrin Dam, and 4000 m3/s, which is the design discharge of Hemrin Dam spillway. A spillway was proposed at the escape entrance with crest level 105m.a.m.s.l., followed by a drop structure with eighteen rectangular steps